Bangla optical character recognition - Noor, Nawsher Ahmed; Habib, S. M. Murtoza (School of Engineering and Computer Science (SECS) , BRAC University, 2010)
This thesis paper is a partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, BRAC University .